Vyuzití PET/CT vysetrení pri plánování radioterapie nádorů ORL oblasti - Kolárová, I; Vanásek, J; Odrázka, K; Petruzelka, L; Dolezel, M; Nechvíl, J (Klinicka onkologie, 2009)
BACKGROUND: Using conformal techniques and IMRT in radiotherapy allows dose increase in the target volume and sparing of healthy tissues. In comparison with conventional techniques it requires more accuracy in the target volume delineation. It is important to use all relevant diagnostic methods to reduce the risk of relapse.The basic method is CT examination which allows the dose distribution to be calculated. New imaging dimensions are associated with PET (positron emission tomography), which supplements the morphological image (CT or MRI) with a functional view.The aim of this study was to evaluate the benefit of PET/CT fusion in radiotherapy planning for head and neck cancer. PATIENTS AND METHODS: 40 head and neck cancer patients treated by definitive radiotherapy were evaluated. The patient group consisted of 30 men and 10 women, with a median age of 56 years (range 34-81 years). Postoperative radiotherapy was used in 10 cases and 30 patients were irradiated without prior surgery. IMRT technique with simultaneous integrated boost was used with 6 MV photons. RESULTS: Comparing diagnostic CT with planning PET/CT, there was no difference in tumour extent in 20 out of 40 patients. In 6 cases (15%) the nodal involvement was more extensive according to PET/CT while in 3 cases (7.5%) the nodal involvement was detected to be less extensive. In 2 patients (5%) the primary tumour was reclassified, in both cases towards tumour enlargement. Two patients with positive histopathological margin were PET/CT negative. PET/CT imaging resulted in a change in the target volume in 11 (27.5%) patients and the treatment strategy was changed in 3 cases. CONCLUSION: We tested use of the PET/CT examination in radiotherapy treatment planning of the head and neck carcinoma and it was introduced as a standard clinical practice at our department.
Keywords: počítačová rentgenová tomografie; Humans; Radiotherapy Planning, Computer-Assisted; lidé středního věku; Female; Aged; dospělí; senioři; lidé; nádory hlavy a krku; Head and Neck Neoplasms; Adult; ženské pohlaví; Male; Middle Aged; Tomography, X-Ray Computed; Radiotherapy, Conformal; plánování radioterapie pomocí počítače; Aged, 80 and over; Positron-Emission Tomography; senioři nad 80 let; konformní radioterapie; mužské pohlaví; pozitronová emisní tomografie